2021
DOI: 10.24966/avs-7397/100059
|View full text |Cite
|
Sign up to set email alerts
|

The Burning Necessity for Establishing National Guidelines - Side Effects of Lipid Lowering Drugs and Difficulty of using High Intensity Statins in Pakistani Population

Abstract: Lipid lowering strategy has been widely used in both the primary as well as the secondary prevention of atherosclerotic cardiovascular disease, particularly in managing patients who are either diagnosed with ischemic heart disease or stroke or face great susceptibility to developing these complications as a result of risk factors like diabetes, hypertension, sedentary lifestyle and so on [1,2]. The mechanism of action of Statins is by inhibition of the enzyme 3-hydroxy-3-methylglutaryl coenzyme A reductase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…While the bene ts of statin therapy remain unmatched, there is also signi cant proof of a number of side effects that come as an unpleasant consequence of statin usage. Statins have been associated with systemic effects like myopathies, hepatotoxicity, type 2 diabetes, polyneuropathies, behavioral changes and GI disturbances with myalgias and tendinopathies being the most common adverse effect which lead to prescription of suboptimal dosage of statins [11]. However, studies have shown that each 1.0 mmol/L reduction in LDL cholesterol results in 11 fewer major cardiovascular events per 1000 treated over 5 years, an advantage that far outweighs any known adverse effects of statin usage [12].…”
Section: Non Adherence To Treatment/guidelinesmentioning
confidence: 99%
“…While the bene ts of statin therapy remain unmatched, there is also signi cant proof of a number of side effects that come as an unpleasant consequence of statin usage. Statins have been associated with systemic effects like myopathies, hepatotoxicity, type 2 diabetes, polyneuropathies, behavioral changes and GI disturbances with myalgias and tendinopathies being the most common adverse effect which lead to prescription of suboptimal dosage of statins [11]. However, studies have shown that each 1.0 mmol/L reduction in LDL cholesterol results in 11 fewer major cardiovascular events per 1000 treated over 5 years, an advantage that far outweighs any known adverse effects of statin usage [12].…”
Section: Non Adherence To Treatment/guidelinesmentioning
confidence: 99%